The association between the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio and delirium in ischemic stroke patients - Pangbo Wang; Pangbo Wang; Jing Huang; Liwei Xu; Rong Hu (Frontiers in Medicine)
BackgroundDelirium is a severe neuropsychiatric symptom following acute ischemic stroke (IS) and is associated with poor outcomes. Systemic inflammation and immune dysregulation are believed to contribute to the pathophysiology of delirium. The neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are widely recognized as convenient and reliable biomarkers of systemic inflammation. However, their association with delirium after IS remains unclear.MethodsIn this study, we identified IS patients requiring ICU admission from the Medical Information Mart for Intensive Care (MIMIC)-IV database. We employed multivariable logistic regression and restricted cubic splines (RCS) to assess the association between the NLR, PLR, and LMR and delirium. Two-sample Mendelian randomization (MR) analysis was performed to further explore their causal relationship at the genetic level.ResultsA total of 1,436 patients with IS were included in this study, of whom 214 (14.9%) had delirium. In the multivariate logistic regression analysis, after adjustment for confounders, the patients in the highest quartile of the NLR (odds ratio [OR] 2.080, 95% confidence interval [CI], 1.282–3.375) and LMR (OR 0.503, 95% CI 0.317–0.798) and the patients in the second quartile of the PLR (OR 1.574, 95% CI 1.019–2.431) were significantly associated with delirium. The RCS function showed a progressive increase in the risk of delirium with higher NLR and PLR and lower LMR. In the MR analysis, only the PLR was negatively associated with the risk of delirium.ConclusionThe observational studies found significant associations between the NLR, PLR, and LMR and delirium. However, the MR analysis only demonstrated a potential protective causal relationship between the PLR and delirium. Further prospective studies are needed to validate their association and to elucidate the underlying mechanisms.